Controlling Chaos with Analysis of Fractional Chaotic System Predicting Respiratory Diseases - Trikha, Pushali; Jahanzaib, Lone Seth; Ahmad, Mudassir (Journal of Applied Nonlinear Dynamics, 2026)
Considering the increasing virus spread in the society, it is important to understand the connection between respiratory illnesses, the prevalence of respiratory viruses, and meteorological conditions in various nations in order to effectively prepare hospital services for admissions. The paper addresses the fractional four dimensional chaotic system predicting respiratory diseases. The system is thoroughly analyzed by using dynamical tools of phase portraits, bifurcation diagrams, Lyapunov diagrams etc. Adaptive SMC method is applied for controlling chaos in presence of uncertainties and disturbances. Theoretical studies is verified numerically using MATLAB.